1994
DOI: 10.1051/lait:1994212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bifidobacterial growth-promoting activity of ultrafiltered casein hydrolyzate fractions

Abstract: Summary -Growth rates and acid production of the most common dairy-related bifidobacteria (Bifidobacterium infantis, B breve and B longum) were determined in the presence of casein hydrolyzates produced by the action of three proteolytic enzymes (alcalase, chymotrypsin and trypsin). Casein hydrolyzates were fractionated with a two-step ultrafiltration process to study the effect of molecular mass of peptides on bifidobacterial growth. The retentate of the second ultrafiltration (nominal molecular eut-off of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…All these results suggested that ultrafiltration is one of the efficient techniques for further isolation of fractions with strong growth‐promoting activity for brewer's yeast from SPH, and the ultrafiltered fraction (Mw < 3 kDa) of SPH was the determinant stimulator to the growth of brewer's yeast, irrespective of the kinds of proteolytic enzymes used. The results were in agreement with the reports that the length of peptides is an important factor for the growth and acid production of lactic acid bacteria (St‐Gelais et al ., ), and small peptides (Mw < 2 kDa) were considered as the best ones for stimulating the growth of bifidobacteria (Proulx et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…All these results suggested that ultrafiltration is one of the efficient techniques for further isolation of fractions with strong growth‐promoting activity for brewer's yeast from SPH, and the ultrafiltered fraction (Mw < 3 kDa) of SPH was the determinant stimulator to the growth of brewer's yeast, irrespective of the kinds of proteolytic enzymes used. The results were in agreement with the reports that the length of peptides is an important factor for the growth and acid production of lactic acid bacteria (St‐Gelais et al ., ), and small peptides (Mw < 2 kDa) were considered as the best ones for stimulating the growth of bifidobacteria (Proulx et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…An inoculum size of 50 ml l −1 was chosen for further experiments as it gave the most reliable set of results. Similar inoculum levels have been applied (Ventling & Mistry 1993; Proulx et al . 1994) and are also recommended as a selection criterion for starters in fermented milk products (Kurmann 1988).…”
Section: Methodsmentioning
confidence: 99%
“…(1993) also found that the length of peptides is an important factor for the growth and acid production of lactic acid bacteria. In addition, Proulx et al. (1994) reported that small peptides (<2000 Da) were the best for stimulating growth of bifidobacteria .…”
Section: Resultsmentioning
confidence: 99%